RAB-A5c GTPase and the regulation of cell geometry during Arabidopsis root organogenesis - Kirchhelle, C (2016)
A fundamental challenge in biology is to explain how different organisms develop the intricate anatomical forms observed in nature. During morphogenesis, biochemical, mechanical, and geometric information has to be integrated across multiple organisational scales, from multicellular organs over individual cells down to subcellular components. In multicellular plants, individual cells are fixed in their relative position in the tissue by their surrounding rigid cell wall. Therefore, plant organogenesis requires control over division plane orientation and anisotropic cell wall growth, which each require spatial patterning of cells. Polyhedral plant cells can display complex patterning in which individual faces are established as biochemically distinct domains by endomembrane trafficking. This thesis shows that the specification of an additional cellular spatial domain by the endomembrane system, a cell’s geometric edges, is crucial for lateral root organogenesis. Membrane vesicles lying immediately beneath the plasma membrane at cell edges were revealed through localisation of RAB-A5c, a plant GTPase of the Rab family of membrane-trafficking regulators. RAB-A5c compartments were enriched at growing edges, and associated with the cortical microtubule array. Specific inhibition of RAB-A5c activity grossly perturbed cell geometry and organ growth in developing lateral organs. Quantitative 4D cell growth analysis revealed RAB-A5c inhibition indedependently caused perturbations of cell growth anisotropy and cytokinesis without disrupting default membrane trafficking. To investigate the underlying mechanism of RAB-A5c-mediated growth regulation, hypotheses for RAB-A5c function in modulating cortical microtubule array orientation and cell wall mechanical properties were tested. Based on a combination of quantitative image analysis, pharmacological and genetic approaches, and mechanical modelling, RAB-A5c is proposed to locally modify cell wall properties during growth, and two possible models for RAB-A5c function and their implications for cell-, tissue- and organ-level growth control are discussed.